2012
DOI: 10.1371/journal.ppat.1002834
|View full text |Cite
|
Sign up to set email alerts
|

AsrR Is an Oxidative Stress Sensing Regulator Modulating Enterococcus faecium Opportunistic Traits, Antimicrobial Resistance, and Pathogenicity

Abstract: Oxidative stress serves as an important host/environmental signal that triggers a wide range of responses in microorganisms. Here, we identified an oxidative stress sensor and response regulator in the important multidrug-resistant nosocomial pathogen Enterococcus faecium belonging to the MarR family and called AsrR (antibiotic and stress response regulator). The AsrR regulator used cysteine oxidation to sense the hydrogen peroxide which results in its dissociation to promoter DNA. Transcriptome analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 91 publications
3
62
0
Order By: Relevance
“…A recent study showed that AsrR-mediated sensing of oxidative stress by Enterococcus influenced levels of antibiotic resistance, interactions with host cells, and virulence (34). Because the mucus layer is exposed to oxygen diffused from the bloodstream and intestinal epithelial cells (35), E. faecium cells might need mechanisms to tolerate oxygen in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that AsrR-mediated sensing of oxidative stress by Enterococcus influenced levels of antibiotic resistance, interactions with host cells, and virulence (34). Because the mucus layer is exposed to oxygen diffused from the bloodstream and intestinal epithelial cells (35), E. faecium cells might need mechanisms to tolerate oxygen in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of deletion mutants. For the construction of the ⌬efau004_01228 strain and in an attempt to delete the efau004_00094 gene, allelic replacements were carried out as previously described (19). Briefly, DNA fragments (obtained by PCR with the chromosomal DNA of E. faecium Aus0004 as the template) containing ligated upstream and downstream sequences of the desired deletion fragment were cloned into the thermosensitive replication plasmid pWS3 (20) (Table 1), and 1 g of recombinant plasmid was used to transform E. faecium Aus0004 competent cells by electroporation.…”
Section: Methodsmentioning
confidence: 99%
“…The deletion mutant was also susceptible to killing in murine macrophages and was less efficient at colonization and dissemination in a murine peritonitis model. AsrR (antibiotic and stress response regulator), an oxidative sensing regulator of the MarR family, was recently described for E. faecium (536). The AsrR regulon consists of genes involved in pathogenesis, antibiotic resistance, oxidative stress, and adaptive responses.…”
Section: Oxidative Stress and Virulencementioning
confidence: 99%